Poly[[tris(N,N-dimethylformamide)-(mu(4)-5-nitroisophthalato)(mu(3)- 5-nitroisophthalato)dicobalt(II)] N,N-dimethylformamide monosolvate] - Su, M.; Huang, Zhan-Dong; Sun, H.; Yang, G.; Ng, S.W. (International Union of Crystallography, 2010)
In the polymeric title compound, [Co-2(C3H7NO)(3)(C8H3NO6)(2)]center dot C3H7NO, one 5-nitroisophthalate dianion has its two carboxylate groups chelating to one Co-II atom while simultaneously coordinating to another metal atom in a mu(4)-bridging mode. The other 5-nitroisophthalte dianion has one carboxylate group chelating to a metal atom whereas the other bridges two metal atoms in a mu(3)-bridging mode. Both metal atoms show an octahedral coordination. The polymer adopts a layer motif, with the lattice dimethylformamide molecules occupying the space between adjacent layers.